(untitled) (African Journal for Industrial and Applied Mathematics, 2025)
Patriotism is a changing, complex force inside a nation, whose manifestations are determined by factors as diverse as success in sports, scientific discoveries, cultural pride, economic development, and the presence of national heroes. This study develops a generalized mathematical model for patriotism as the sum of these effects, both emotional and enduring. In particular, the model records surges in patriotism after major sporting victories due to the transience of these surges, for instance, after the victory of the Indomitable Lions or the boxing exploits of Francis Ngannou. In contrast, the model also underlines the long-lasting characteristics of patriotism shaped by scientific progress, such as a Cameroonian being ranked high in mathematics, cultural legacy, infrastructure expansions, and economic development. The sports effect is a series of ephemeral spikes in patriotic sentiment triggered by importance and emotional resonance. In contrast, both the science and infrastructure effects are slowly cumulative processes that build a longer foundation of national pride. These effects, alone and in combination, are shown in the visualizations of their contributions to patriotism over time. This work emphasizes the importance of acknowledging and effectively harnessing these myriad influences for a strong, cohesive nation. The insights are actionable, helping leaders to stimulate a rational yet productive sense of patriotism that is engaged with national development, starting with emotional stimuli but progressing to more permanent investments.